A case report: Ayurvedic intervention in motor neuron disease contemplating Kaphavrutavata - Basavaraj V. Policepatil (Journal of Ayurveda and Integrative Medicine, 2022)
Motor neuron disease (MND) otherwise referred as Amyotrophic lateral sclerosis (ALS) affects human life in various ways. ALS with multifocal onset might exhibit muscle stiffness and muscle weakness of upper and lower limbs, muscle twitching, atrophy, falling/tripping, slurred speech, difficulty in swallowing and loss of dexterity. In Ayurvedic contexts Avarana vatavyadhis are found to have close resemblance to MND. The patient presented with features of multifocal onset of ALS which can be related to Kaphavruta Udanavata. The treatment principle of kaphavarana including Swedana (∼sudation), Niruhabasti (∼medicated enema), Vamana (∼therapeutic emesis) Virechana (∼purgation) and Sarpipana (∼oral intake of medicated ghee) along with other oral medications have been explained in Ayurvedic texts. In the present study, the same treatments were administered except for vamana due to patient's unwillingness. The Functional Rating Scale for ALS (ALSFRS-R) was used for assessment. The ALSFRS-R score before the treatment was 29 which was increased to 38 with remarkable improvement in Salivation and moderate improvement in Speech, Swallowing, Walking, Climbing stairs, Dyspnea and Orthopnea. The treatment was found to be highly effective in preventing the late stage complications which usually occur within 1–2 years of the disease onset and thereby helps the patient to be self-reliant.